Разработка эффективной системы диагностики и профилактики дистресса плода путем изучения метаболических процессов у беременных с гипертензивными расстройствами и плацентарной недостаточностью = An effective system of fetal distress diagnosis and prevention development by metabolic processes in pregnant women with hypertensive disorders and placental insufficiency investigation - Gaystruk, N. A.; Mazchenko, O. O. (Journal of Education, Health and Sport, 2016)
Gaystruk N. A., Mazchenko O. O. Разработка эффективной системы диагностики и профилактики дистресса плода путем изучения метаболических процессов у беременных с гипертензивными расстройствами и плацентарной недостаточностью = An effective system of fetal distress diagnosis and prevention development by metabolic processes in pregnant women with hypertensive disorders and placental insufficiency investigation. Journal of Education, Health and Sport. 2016;6(6):155-176. eISSN 2391-8306. DOI http://dx.doi.org/10.5281/zenodo.55172 http://ojs.ukw.edu.pl/index.php/johs/article/view/3567 The journal has had 7 points in Ministry of Science and Higher Education parametric evaluation. Part B item 755 (23.12.2015). 755 Journal of Education, Health and Sport eISSN 2391-8306 7 © The Author (s) 2016; This article is published with open access at Licensee Open Journal Systems of Kazimierz Wielki University in Bydgoszcz, Poland Open Access. This article is distributed under the terms of the Creative Commons Attribution Noncommercial License which permits any noncommercial use, distribution, and reproduction in any medium, provided the original author(s) and source are credited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. This is an open access article licensed under the terms of the Creative Commons Attribution Non Commercial License (http://creativecommons.org/licenses/by-nc/4.0/) which permits unrestricted, non commercial use, distribution and reproduction in any medium, provided the work is properly cited. The authors declare that there is no conflict of interests regarding the publication of this paper. Received: 05.05.2016. Revised 25.05.2016. Accepted: 25.05.2016. УДК 618.36;618.3-16,155.194.5.021 РАЗРАБОТКА ЭФФЕКТИВНОЙ СИСТЕМЫ ДИАГНОСТИКИ И ПРОФИЛАКТИКИ ДИСТРЕССА ПЛОДА ПУТЕМ ИЗУЧЕНИЯ МЕТАБОЛИЧЕСКИХ ПРОЦЕССОВ У БЕРЕМЕННЫХ С ГИПЕРТЕНЗИВНЫМИ РАССТРОЙСТВАМИ И ПЛАЦЕНТАРНОЙ НЕДОСТАТОЧНОСТЬЮ Н. А. Гайструк, О. О. Мазченко Винницкий национальный медицинский университет имени Н. И. Пирогова, Винница Резюме Представленная статья посвящена изучению современных исследований, которые касаются этиопатогенетических особенностей развития дистресса плода у беременных с плацентарной недостаточностью. Проведенный анализ научных работ позволяет допустить, что разбалансирование регуляторных факторов многих систем организма у беременных с плацентарной недостаточностью может инициироваться дефицитом окислительных соединений азота, что приводит к усилению окислительной деструкции белков, что в свою очередь, может приводить к их деполимеризации, нарушений не только мембранно-транспортных функций клеток, но и к гибели последних. При этом не исключена возможность индукции процессов апоптоза клеток плаценты, что может играть решающую роль в развитии плацентарной недостаточности, а значит, осложненном течении беременности. Оксид азота, влияя на процессы дилятации сосудистого русла, а значит на процессы оксигенации организма, при его дефиците может играть роль пускового механизма в срыве компенсаторных реакций в системе мать-плацента-плод. Дефицит оксида азота может возникать вследствии гипергомоцистеинэмии и гипоксии печени, уменьшения синтеза оксида азота, или повышения его использовання при возрастании активных форм кислорода, развития оксидативного стресса. Изучено причины возникновения дистресса плода у беременных с гипертензивными расстройствами, разработаны методы диагностики и профилактики этой патологии беременности. Ключевые слова: гипертензивные расстройства беременных, биохимическая альтерация, дистресс плода, гипергомоцистеинэмия, окислительная модификация белков, плацентарная недостаточность, актовегин. AN EFFECTIVE SYSTEM OF FETAL DISTRESS DIAGNOSIS AND PREVENTION DEVELOPMENT BY METABOLIC PROCESSES IN PREGNANT WOMEN WITH HYPERTENSIVE DISORDERS AND PLACENTAL INSUFFICIENCY INVESTIGATION N. A. Gaystruk, O. O. Mazchenko N. I. Pirogov Vinnitsa National Medical University, Vinnitsa Summary This representative article is devoted to learning modern investigations, which belong to ethiopathogenetic peculiarities of fetal distress development in the pregnant women placental insufficiency. The analysis of scientific works allows to assume that regulatory factors disorder of many systems of the organism in pregnant women with hypertension can be initiated by nitrogen oxide compound deficiency, which leads to protein oxidized destruction increasing. This protein destruction leads to its depolymerization, disorder not only of membrane-transportal function of the cells, but to death of the last ones. In this case the indication of the apoptosis of the placenta’s cells is possible, which can play the major role placentary disorder development, and as the result to complicated course of the pregnancy. Nitrogen oxide has ability to influence on dilatation of vessels and oxygenation processes of the organism. Nitrogen oxide deficiency can play the role of the starting of compensatory mechanism disorder in the mother-placenta-fetus system. Nitrogen oxide deficiency may be as the result of the hyperhomocysteinenia, liver hypoxia, decreasing of nitrogen oxide synthesis or increasing its using during elevation of oxygen active forms, oxidative stress. The authors research the courses of the development of the fetal distress in pregnant women with hypertensive disorders, work the methods of the diagnostic and prevention of this pathology. Key words: pregnant women with hypertensive disorders, biochemical alterations, fetal distress, hyperhomocysteinemia, oxygen modification of proteins, placentary failure, actovegin.